1975
DOI: 10.1021/jo00896a033
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical transformations of small ring heterocyclic systems. LX. Photochemical ring-opening reactions of substituted chromenes and isochromenes

Abstract: the three stereoisomers. The results of this experiment are recorded in Table IV.Photostationary State Compositions from Irradiations of ltt with Various Triplet Sensitizers. Spectrograde cyclohexane solutions of trans,trarcs-bis(/3-styryl)dimethylsilane (1.0 X 10-2 M) and the various triplet sensitizers (acetone, benzophenone, 1-acetonaphthone, and benzil), each 2.0 X ID-2 M, were placed individually in Pyrex test tubes and irradiated with Pyrex-filtered light until the photostationary states were obtained. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…An improvement of the photochromic properties was obtained mainly by using benzo-annulated chromenes, namely the naphthopyrans. Moreover, ' several studies have undoubtedly shown that the alkyl groups at the sp3-C-atoms should be replaced by a spiroadamantane moiety [12] [13], a cyclopropyl group [14] [15], or two aryl substituents to manifest photochromic behaviour at room temperature [16] [17] and to prevent rapid fatigue under photoexcitation [18]. During our study in the field of photoresponsive systems, we reasoned that 2,2-diaryl-2H-chromenes would be a good parent system for such species.…”
Section: Synthesis and Photochromic Behaviour Of Naphthopyrans Pyranmentioning
confidence: 99%
“…An improvement of the photochromic properties was obtained mainly by using benzo-annulated chromenes, namely the naphthopyrans. Moreover, ' several studies have undoubtedly shown that the alkyl groups at the sp3-C-atoms should be replaced by a spiroadamantane moiety [12] [13], a cyclopropyl group [14] [15], or two aryl substituents to manifest photochromic behaviour at room temperature [16] [17] and to prevent rapid fatigue under photoexcitation [18]. During our study in the field of photoresponsive systems, we reasoned that 2,2-diaryl-2H-chromenes would be a good parent system for such species.…”
Section: Synthesis and Photochromic Behaviour Of Naphthopyrans Pyranmentioning
confidence: 99%
“…Indeed, the first described chromenes, 2,2-dimethyl-[2H]-chromenes and their 2H-1Benzo~~rans (or 2H-chr0menes) are an benzoannulated derivatives (naphthopyrans), showed photoparticularly attractive because chromic behavior only at low temperature (2) and, moreover, of their P~~~~~~~~~~~ properties. Indeed, 2H-chromenes led to undesirable by-products (4). In fact, interest in research a ring of the pyran (2).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the spectra of the open forms of the angular compounds 5a and 5b (annellation 5,6) with compound 7 it is possible to conclude that the methyl group of the benzene ring increases the bathochromic effect for λ 2 of 10 nm and the colourability in both wavelengths is slightly increased. A comparison could also be done between compound 5a and the corresponding benzothieno-2H-chromene 8 prepared and studied by some of us 16 (Fig 2), having the same type of annellation (5,6) and the same regio-isomery (S- The presence of the methoxy groups in the benzene rings of the sp 3 carbon of compound 5b had a bathochromic effect in both wavelengths and the colourability increases significatively in both cases comparing to 5a (Table 1). (Fig 1.).…”
Section: Photochromic Propertiesmentioning
confidence: 99%
“…In order to gain reasonable stability of the coloured forms and to prevent rapid fatigue under photoexcitation, it is required to introduce bulky substituents into the 2-position of the pyran ring especially phenyl groups. 5,6 Several five membered 5,6 heteroannellated 2H-chromenes have been prepared and the effect of the heteroannellation on their photochromism was determined. 7 Angular 2H-chromenes heteroannellated at 5,6 and 7,8 positions with a 2,3-dimethylthiophene ring were prepared by us earlier and their photochromic behaviour was studied.…”
Section: Introductionmentioning
confidence: 99%